Strategies in neonatal care to promote optimized growth and development : focus on low birth weight infants, May 26-28, 2021 - Nestlé Nutrition Workshop 2021 : Online); Berrington, Janet E.; Bloomfield, Frank H.; Bode, Lars; Carvalho, Ryan S.; Chmelova, Kristina; Embleton, Nicholas D.; Haschke, Ferdinand 1948- (Switzerland : Karger, 2022)
Early and adequate nutritional support is critical to achieve appropriate rates of weight gain, which are almost twice that of a term infant. The 96th Nestlé Nutrition Institute Workshop was focused on the latest scientific knowledge in the area of neonatal care in preterm and low-birth-weight infants, including human milk oligosaccharides (HMOs) and their potential impact on the health of neonates. This 3-session workshop facilitated interactions between international experts. The first session, chaired by Prof. Nick Embleton, looked at optimizing feeding, nutrition, and growth in the neonatal intensive care unit and after discharge. Prof. Ferdinand Haschke chaired the second session, which looked at the personalized nutrition of preterm infants. The third session, chaired by Lars Bode, looked at the role of HMOs and the microbiome in the health of term and very-low-birth-weight infants. The key issues provided by this 3-day workshop offer valuable insights for healthcare providers, policy makers, and researchers on the crucial role of proper nutrition for adequate growth and consequent development of preterm infants.
La función de los autores fue determinada por el catalogador
Keywords: NIÑOS PREMATUROS -- NUTRICION -- CONGRESOS; BAJO PESO AL NACER -- CONGRESOS